THE EFFECTIVENESS OF E-LITRANS TOOL FOR TRANSLATING FIGURES OF SPEECH FROM INDONESIAN INTO ENGLISH - Rudi - Hartono (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
Difficulties in translating figures of speech should not be allowed to occur for a long time. There must be an effort to solve the problem immediately. Introducing electronic devices to facilitate the translation of figures of speech in the form of a transtool is an important effort to do. One of the efforts is to use the E-Litrans Tool as an electronic device that can improve the quality of the figures of speech translation. This trans tool was tested in experimental research of translating figures of speech from Indonesian to English and vice versa. Three figures of speech, metaphor, simile, and personification, were focused to analyze in this research because they are more widely used in everyday life in the Indonesian context. The three types of figures of speech are arranged into a set of test items, each consisting of 5 pieces so that there are 15 figures of speech. One set of test items was given to the experimental group and the control group. The experimental group consisted of 22 students while the control group consisted of 25 students. All of these students came from translation classes that we taught. The experimental group was treated using the E-Litrans Tool in translating figures of speech, while the control group was not. Based on the research results, it was known that the E-Litrans Tool was able to significantly improve the translation quality of the experimental group. The average translation quality score of the experimental group after using the E-Litrans Tool increased from 60.2 to 95.8. It means that there was an increase in the average value of 35.6. So the overall mean score of their translation quality is 78.36. The translation quality for the control group that did not use the E-Litrans Tool was insignificant and dropped drastically. The mean pretest and posttest scores were 56.88 and 55.84 or the overall mean score of their translation quality was 56.4 without the progress, even dropped decreasingly up to 1.04. It can be concluded that E-Litrans Tool increased the figures of speech translation quality scores significantly. Therefore, we suggest that translators can use the E-Litrans Tool to improve the quality of their figures of speech translation results.